Fundamentos de conectividade para o ensino médio e aplicações dos teoremas de Menger e Festinger - Barros, Marcos Barbosa de (2015)
The present dissertation aims to introduce students to high school useful math concepts connectivity problems using graph theory. After the explanation of basic concepts, we introduce the notion of connectedness, Mengers theorem and we present the theorem of Festinger, which is a useful tool for path counts. We also present an application of these concepts in the analysis of electrical sub-distribution network in the state of Sergipe. Finally we conclude this work by suggesting some didactic sequences for high school students addressing the Euler's theorem for graphs, the themes of connectedness, connectivity, Menger's theorem and the theorem Festinger.